Network Pharmacology, Molecular Docking, and Molecular Dynamics Analysis of Honokiol against Triple-negative Breast Cancer - Hassan H. Alhassan (Hail Journal of Health Sciences)
Introduction: Triple-negative breast cancer (TNBC) persists as a formidable clinical obstacle due to its aggressive nature and the scarcity of effective treatment modalities. Natural compounds have garnered significant interest as potential therapeutic agents against TNBC due to their diverse pharmacological activities. Honokiol, a biphenolic compound derived from Magnolia species, has shown promise as a candidate for TNBC therapy. The current study carried out a multidisciplinary study integrating network pharmacology, molecular docking, and molecular dynamics analysis to elucidate the molecular mechanisms underlying the anticancer effects of honokiol against TNBC. Through network pharmacology analysis, potential protein targets and signaling pathways were identified to be associated with the activity of honokiol. Molecular docking simulations revealed the binding modes and affinity of honokiol with key target proteins (AKT1, PARP1, MDM2, CCND1, CCNB1, EGFR, GSK3B, HDAC1, HSP90AA1, and CDK1) implicated in TNBC progression. Furthermore, molecular dynamics simulations provided insights into the dynamic interactions between honokiol and HSP90AA1 and AKT1 proteins, elucidating the stability and flexibility of the protein–ligand complexes. The findings of the present study shed light on the therapeutic potential of honokiol against TNBC and provide a rationale for its further development as a promising anticancer agent. This integrative approach underscores the significance of natural products in drug discovery and highlights honokiol as a promising candidate for TNBC therapy. Context: TNBC presents a significant challenge in clinical practice due to its aggressive behavior and limited treatment options. Natural compounds have emerged as potential therapeutic avenues, with honokiol, derived from Magnolia species, showing promise against TNBC. Aims: This study aimed to explore the molecular mechanisms underlying honokiol’s anticancer effects against TNBC through a multidisciplinary approach integrating network pharmacology, molecular docking, and molecular dynamics analysis. Settings and Design: The study employed a multidisciplinary approach, combining network pharmacology analysis, molecular docking simulations, and molecular dynamics simulations to elucidate the molecular mechanisms of honokiol against TNBC. Materials and Methods: Network pharmacology analysis was used to identify potential protein targets and signaling pathways associated with honokiol’s activity. Molecular docking simulations were conducted to determine the binding modes and affinity of honokiol with key target proteins implicated in TNBC progression, including AKT1, PARP1, MDM2, CCND1, CCNB1, EGFR, GSK3B, HDAC1, HSP90AA1, and CDK1. Molecular dynamics simulations provided insights into the dynamic interactions between honokiol and HSP90AA1 and AKT1 proteins, elucidating the stability and flexibility of the protein–ligand complexes. Statistical Analysis Used: NA. Results: The study identified potential protein targets and signaling pathways associated with honokiol’s activity against TNBC through network pharmacology analysis. Molecular docking simulations revealed the binding modes and affinity of honokiol with key target proteins implicated in TNBC progression. Molecular dynamics simulations provided insights into the dynamic interactions between honokiol and HSP90AA1 and AKT1 proteins, highlighting the stability and flexibility of the protein–ligand complexes. Conclusions: The findings highlight the therapeutic potential of honokiol against TNBC and support its further development as an anticancer agent. This integrative approach underscores the importance of natural products in drug discovery and positions honokiol as a promising candidate for TNBC therapy.